Boards' strategic involvement models: Past, present, and future - Bozhinovska Tihona; Eftimov Ljupcho (Strategic Management)
Background: The research on boards' strategic involvement has increased dramatically in the last few decades due to the need for improving boards' strategic effectiveness as a mechanism for improving organizational performance. The corporate scandals highlighted even more that boards' strategic decisions have sizable consequences for organizational survival, and long-term implications for organizational development. Purpose: The main research questions in this study are: 1. Which are the main elements of the concept of boards' strategic involvement?; 2. Which models constitute the core of the concept and how we can classify them?; 3. How has the discourse on boards' strategic role changed over time? Our purpose is to provide comprehensive answers to these questions and draft the future research agenda in this area. Study design/methodology/approach: Having in mind that boards' strategic involvement is a multi-disciplinary area, we first conducted an integrative literature review, to detect the competing groups of models, and afterwards we conducted a semi-structured literature review in order to identify the most important topics in this area and to draft the future research agenda. Findings/conclusions: This paper contributes to research by identifying the models of boards' strategic involvement, classifying them in three competing groups of models that represent the foundation in this research area, by identifying the most investigated topics in the past five years and finally, by drafting the future research agenda. Our conclusion is that the research in this multidisciplinary area is navigating around these three groups of models and that the most explored topics around which the future research is going to be conducted are boards' involvement in the area of strategic human resource management and decisions regarding organizations' sustainability. Limitations/future research: The study's main limitations are related to the fact that the identified models on boards' strategic involvement have been developed, mostly by authors from the USA and UK, where the one-tier board system is used. In future research, the authors should focus on proposing new framework(s)/model(s) and supporting its insights with empirical evidence.